Therapeutic improvement of colonic anastomotic healing under complicated conditions: A systematic review - Nerstrøm, Malene (World J Gastrointest Surg, 2016)
AIM: To identify therapeutic agents for the prophylaxis of gastrointestinal anastomotic leakage (AL) under complicated conditions. METHODS: The PubMed and EMBASE databases were searched for English articles published between January 1975 and September 2014. Studies with the primary purpose of improving anastomotic healing in the colon or rectum under complicated preoperative and/or intraoperative conditions were included. We excluded studies investigating the adverse effects or risk assessment of an active intervention. Furthermore, investigations of biophysical materials, sealants, electrical stimulation and nutrients were excluded. The primary study outcome was biomechanical anastomotic strength or AL. The meta-analysis focused on therapeutic agents that were investigated in one animal model using the same outcome by at least three independent research groups. RESULTS: The 65 studies included were divided into 7 different complicated animal models: Bowel ischemia, ischemia/reperfusion, bowel obstruction, obstructive jaundice, peritonitis, chemotherapy and radiotherapy. In total, 48 different therapeutic compounds were examined. The majority of investigated agents (65%) were reported as beneficial for anastomotic healing. Twelve of the agents (25%) were tested more than once in the same model, whereas 13 (27%) of the agents were tested in two or more models of complicated healing. Two therapeutic agents met our inclusion criteria for the meta-analysis. Postoperative hyperbaric oxygen therapy significantly increased anastomotic bursting pressure in ischemic colon anastomoses by a mean of 28 mmHg (95%CI: 17 to 39 mmHg, P < 0.00001). Granulocyte macrophage-colony stimulating factor failed to show a significant increase in anastomotic bursting pressure (95%CI: -20 to 21 mmHg, P = 0.97) vs controls in experimental chemotherapeutic models. CONCLUSION: This systematic review identified potential therapeutic agents, but more studies are needed before concluding that any of these are useful for AL prophylaxis.